Political Landscapes of Capital Cities - Guzmán, Eulogio; Bogdanović, Jelena, 1973-; Christie, Jessica Joyce, 1956- (Book collections on Project MUSE., 2016)
"Investigates the transformation of landscapes into culturally constructed and ideologically defined political environments of capital cities. In this spatially inclusive, socially dynamic interpretation, an interdisciplinary group uses a methodology to expose the associations between human-made environments and the natural landscape that accommodate socio-political needs of governmental authority"--